Rehabilitation of the spine : a a patient-centered approach - Craig Liebenson (Philadelphia, Pennsylvania : Wolters Kluwer, 2020)
"The gold standard resource in the field, Rehabilitation of the Spine: A Patient-Centered Approach provides a practical overview of all aspects of spinal rehabilitation. The 3rd Edition has been completely revised, with new information and new videos to bring you up to date. Comprehensive and easy to read, this reference is invaluable for chiropractors and physical therapists, as well as spine surgeons, physician assistants, and nurse practitioners involved in the care of patients with spine problems."--Provided by publisher
Keywords: Back Pain rehabilitation; Exercise Therapy; Chiropractic; Backache Exercise therapy